Queen bee [large type] : a novel - Frank, Dorothea Benton ([Lowcountry tales, 2019)
A Sullivan's Island beekeeper navigates her demanding hypochondriac mother and flamboyant rival sister while immersing herself in the lives of two young neighbor boys and their widowed father.